DEVELOPING LANGUAGE COURSES TO PREPARE STUDENTS FOR INTERNATIONAL SCIENTIFIC CONFERENCES - Narbayeva Malohat Xudayberdiyevna (International Scientific and Current Research Conferences, 2024)
Language proficiency is a critical factor in preparing students for participation in international scientific conferences, where effective academic communication is key to sharing research and engaging with global audiences. This article explores the challenges students face, such as limited exposure to academic language and inadequate training in oral and cross-cultural communication. It proposes strategies for designing specialized language courses that focus on academic writing, speaking, and cultural competence. Practical approaches, including mock conferences, interactive workshops, and peer review, are discussed to enhance student readiness. The article also emphasizes the role of institutions in providing support, resources, and continuous evaluation of training programs. By addressing these aspects, the study aims to bridge the language gap and empower students to succeed on international academic platforms.